2006
DOI: 10.1103/physrevb.73.235108
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic BCS-BEC crossover at finite temperature: Effects of repulsion and electron-hole mass difference

Abstract: The BCS to Bose-Einstein condensation (BEC) crossover of electron-hole (e-h) pairs in optically excited semiconductors is studied using the two-band Hubbard model with both repulsive and attractive interactions. Applying the self-consistent t-matrix approximation combined with a local approximation, we examine the properties of a normal phase and an excitonic instability. The transition temperature from the normal phase to an e-h pair condensed one is studied to clarify the crossover from an e-h BCS-like state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(68 citation statements)
references
References 38 publications
7
60
1
Order By: Relevance
“…Electrons and holes in solids involve not only the e-h attractive Coulomb interaction U but also the repulsive n=0.25 Figure 5 The condensation temperature T c as a function of U for U = 0, 1, and 2 at n = 0.25 and γ ≡ t h /t e = 1 [12]. The dotted line denotes the result from the BCS theory.…”
Section: Phase Diagram At Finite Temperature: Dmft Calculationmentioning
confidence: 96%
“…Electrons and holes in solids involve not only the e-h attractive Coulomb interaction U but also the repulsive n=0.25 Figure 5 The condensation temperature T c as a function of U for U = 0, 1, and 2 at n = 0.25 and γ ≡ t h /t e = 1 [12]. The dotted line denotes the result from the BCS theory.…”
Section: Phase Diagram At Finite Temperature: Dmft Calculationmentioning
confidence: 96%
“…(15) indicates that the phase stiffness in the system of excitonic pairs is characterized by an energy scale proportional to ∆t e t h /(t e + t h ) for all the values of the Coulomb interaction parameter U and it is related to the motion of the center of mass of e-h composed quasiparticle, because t e t h /(t e + t h ) ≈ (m e + m h ) −1 [9] implying that the exchange coupling parameter becomes proportional to the excitonic BEC critical temperature [9,19]. The numerical evaluations of J for the case T = 0 are shown in Fig.…”
Section: Phase Stiffness and Condensationmentioning
confidence: 99%
“…[9], where it is shown that the excitonic insulator state is an excitonium state, where the incoherent e-h bound pairs are formed, and furthermore, at lower temperatures, the BEC of excitons appears in consequence of reconfiguration and coherent condensation of the preformed excitonic pairs. In the whole BCS-BEC transition region the e-h mass difference leads to a large suppression of the BEC transition temperature, which is proved to be not the same as the excitonic pair formation temperature [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13]. The inclusion of an interlayer or interband interaction opens the possibility of exciton formation and condensation, which has been studied using determinantal Monte Carlo simulations [14], exact diagonalization [15], DMFT [16,17], and various other theoretical approaches [18,19].…”
Section: Introductionmentioning
confidence: 99%